AB0182 Glucocorticoid therapy underestimates the disease activity index of rheumatoid arthritis during biologic therapy. (23rd January 2014) - Kanda, M.; Kondo, M.; Mukai, M.
Abstract : Background: Since 1950s, glucocorticoid (GC) has been used to relieve the symptom of rheumatoid arthritis (RA). Recent studies showed short term GC therapy is effective to retard the articular destructions (COBRA, BeSt, and CAMERA-II) 1 )2 )3 ) . However, it has been not well known the efficacy of the chronic GC usage, especially with biologics. Objectives: To evaluate the effect of the chronic GC usage with biologics for the disease activity index and joint damage in RA patients Methods: Patients with RA treated by one biologic agent for about one year (9 months to 15 months) were candidates for the evaluation. Patients treated by new biologics within 6 month prior to the beginning of the observation period were excluded. At the beginning of the observation period, sharp/ van der Heidji score (TSS) and disease activity score (DAS28CRP, DAS28ESR, CDAI, and SDAI) was collected. In addition, delta-TSS per year (ΔTSS/Y) was evaluated, retrospectively. All participants were divided into four groups, group A (without GC therapy, with structural remission (ΔTSS/Y under 0.5)), group B (without GC therapy and without structural remission) group C (with GC therapy and structural remission), and group D (with GC therapy and without structural remission). Results: 52 patients (including six males) were included and divided into the four groups (group A: 18, group B: 9, group C: 14, and group D: 11). 48 patients were received methotrexate therapy. Median dose of the GC therapy was equivalent as prednisolone 5 mg per day (2-5mg per day). 20 patients were treated by etanercept, 18 patients infliximab, seven adalimumab, four abatacept, and three tocilizumab. Median disease duration was nine years (1-32 years). Median ΔTSS/Y was 0 point/year (0-3 points/year). At the baseline, there was no difference in the background factors among the four groups. Without GC therapy, the lower disease activity index was a good predictive factor of structural remission (DAS28CRP 1.1 [1.0-2.9] (group A) vs. 2.0 [1.0-3.9] (group B) (p = 0.026)); however, with GC therapy, the disease activity index cannot predict structural remission (DAS28CRP 2.6[1.1-3.5] (group C) vs. 1.1 [1.9-3.0] (group D) (p = 0.42)). Conclusions: The disease activity index cannot predict structural remission, especially in cases with chronic CG therapy during biologic therapy. References: Bakker M.F., Jacobs J.W., Welsing P.M., et al.: Low-dose prednisone inclusion in a methotrexate-based, tight control strategy for early rheumatoid arthritis: a randomized trial. Ann Intern Med, 156: 329-339, 2012. Goekoop-Ruiterman Y.P., De Vries-Bouwstra J.K., Allaart C.F., et al.: Clinical and radiographic outcomes of four different treatment strategies in patients with early rheumatoid arthritis (the BeSt study): a randomized, controlled trial. Arthritis Rheum, 52: 3381-3390, 2005. Landewe R.B., Boers M., Verhoeven A.C., et al.: COBRA combination therapy in patients with early rheumatoid arthritis: long-term structural benefits of a brief intervention. Arthritis Rheum, 46: 347-356, 2002. Disclosure of Interest: None Declared